Structure-function analysis of rgs1 in magnaporthe oryzae : role of DEP domains in subcellular targeting - Ramanujam, Ravikrishna. (2013)
Rgs1, a prototypical Regulator of G protein Signaling, negatively modulates the cyclic AMP pathway thereby influencing various aspects of asexual development and pathogenesis in the rice-blast fungus Magnaporthe oryzae. Rgs1 possesses tandem DEP motifs (termed DEP-A and DEP-B; for Dishevelled, Egl-10, Pleckstrin) at the N-terminus, and a Gα-GTP interacting RGS catalytic core domain at the C-terminus. In this study, we focused on gaining further insights into the mechanisms of Rgs1 regulation and subcellular localization by characterizing the role(s) of the individual domains and the full-length protein during asexual development and pathogenesis in Magnaporthe. Methodology/Principal Findings: Utilizing western blot analysis and specific antisera against the N- and C-terminal halves of Rgs1, we identify and report the in vivo endoproteolytic processing/cleavage of full-length Rgs1 that yields an N-terminal DEP and a RGS core domain. Independent expression of the resultant DEP-DEP half (N-Rgs1) or RGS core (C-Rgs1) fragments, failed to complement the rgs1Δ defects in colony morphology, aerial hyphal growth, surface hydrophobicity, conidiation, appressorium formation and infection. Interestingly, the full-length Rgs1-mCherry, as well as the tagged N-terminal DEP domains (individually or in conjunction) localized to distinct punctate vesicular structures in the cytosol, while the catalytic RGS core motif was predominantly vacuolar.